Pengaruh JUB, Suku Bunga, Inflasi, Ekspor dan Impor terhadap Nilai Tukar Rupiah atas Dollar Amerika Serikat - Nurul Hazizah; Sebastiana Viphindrartin; Zainuri Zainuri (UPT Penerbitan Universitas Jember, 2017)
Fluctuations of exchange rate against Rupiah to U.S Dollar which unstable are influenced the domestic and foreign’s economicconditions. Macroeconomic conditions in the two countries both Indonesia and United States can make the exchange ratedepreciate or appreciate. The purpose of this research is to acknowledge the difference impact macro variables in both countriesIndonesia and the United States against the value on rupiah to US Dollar. Dynamic model is applied in this research that isPartial Adjustment Model (PAM). This model is considered to existing inertia variable that is expectation of exchange rateinfluence by the value of exchange rate that occurred previously. There are two analysis is descriptive analysis and causalanalysis. Causal is using Ordinary Least Square (OLS) method. OLS estimation of PAM shows all independent variable havepositive impact to the exchange rate expectation besides difference Export variable, in addition the difference of the interest ratevariable can’t influence the exchange rate significantly on important of the exchange rate expectation. In conclusion, theinterest rate policy is considered to influence the rupiah exchange rate if two countries do not change the interest ratesimultaneously and other macro policy variables must bring into line.